Mô hình văn hóa an toàn thông tin kế toán: Một nghiên cứu thực nghiệm tại Việt Nam - Phạm Trà, Lam; Đậu Thị Kim, Thoa; Nguyễn Phước Bảo , Ấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
In the complex digital world, businesses have invested in advanced security technologies and other mechanisms that support information security (IS), especially accounting information security, because of the increasing ramifications and diversity of threats, which are increasing and changing constantly. Building an information security culture (ISC) is considered a highly effective approach. Therefore, this study developed a structural model including the four dimensions of ISC which are accounting IS attitudes, awareness, competencies, and behavior (ISB). Data collected from 181 employees are analyzed by the PLS proving that information security awareness and competencies strongly impact behavior intention. These structures of the ISC create significant contributions to the ISB. The findings provide new insights about ISC, providing managers with implications for successful accounting information security.